Hubungan Kebiasaan Merokok Dengan pH Saliva Pada Mahasiswa Perokok di Asrama Mahasiswa Kalimantan Selatan di Yogyakarta - Siti Fatimah; Herastuti Sulistyani; Aryani Widayati (Journal of Oral Health Care, 2018)
Long-term smoking effects can cause a decrease in salivary pH to be more acidic. To investigate the correlation of smoking habit and salivary pH on smoker students in the South Kalimantan Student Dormitory in Yogyakarta. This research is an analytical survey with a cross-sectional design, sampling was done by purposive sampling method and the sample used was 39 smoking students who have smoked with a minimum period of 1 year. The results were analyzed using Kendall-Tau correlation test with SPSS program. Smoking habits in the student smokers are included in heavy smoking habits (61.5%), whereas saliva pH was mostly included in the acid salivary pH criteria (64.1%). Results of cross-tabulation as many as 56.4% of smoker students have a heavy smoking habit with acid salivary pH. The test of statistical analysis obtained significance value (p) of 0.000 with Kendall-Tau correlation coefficient of -0.727. The p-value (0.000) < 0.05, meaning that the results showed a significant relationship between smoking habit and salivary pH. There is a significant correlation between smoking habit and salivary pH on smoker students in the South Kalimantan Student Dormitory in Yogyakarta.